Meta-Analysis of the Effects of Stress and Anxiety on Alcohol Consumption Behavior in Early Adults - Windya Kartika Paramita; Argyo Demartoto; Hanung Prasetya (Journal of Health Promotion and Behavior, 2023)
Background: Consumption of alcoholic beverages is a risk factor for health problems globally.  The consumption of alcoholic beverages is very influential on the effect of calmness in people who have anxiety and stress disorders. The effect occurs because alcohol is classified as a psychoactive substance that affects nerves in the brain with the effect of dependence on the dose consumed.  This study aims to assess the effect size of stress and anxiety on increased alcohol consumption behavior in early adulthood using a meta-analysis of primary studies conducted by the previous authors. Subjects and Method: This study was a meta-analysis with the following PICO, population: Early adults (18-25 years). Intervention: Stress and Anxiety. Comparison: no stress and no anxiety.  Result: Increased Alcoholic Beverages Consumption Behavior.  9 The articles used in this study were obtained from three databases namely Google Scholar, PubMed, and Scopus. The keywords for searching for articles were stress AND (Anxiety OR nervousness OR discomfort) AND ("consumption of drinking alcohol" OR "Alcohol use").  The included articles were full-text English with a cross-sectional study design from 2012 to 2022. Article selection was conducted using the PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 app. Results: A total of 9 cross-sectional case studies from Europe, Asia, North America, Africa, and Australia were selected for systematic review and meta-analysis.  7 studies discovered that stress increased alcoholic beverage consumption behavior in early adults by 1.29 times compared to low stress, and the result of the meta-analysis was statistically significant (aOR= 1.29; CI 95%= 1.31-1.47; p< 0.001) with the heterogeneity of I2= 84%, p<0.001. 7 studies of the effect of anxiety on increased alcoholic beverage consumption behavior in early adults showed anxiety increased alcoholic beverage consumption behavior in early adults by 1.59 times compared to low anxiety.  The result of the meta-analysis was statistically significant (aOR= 1.59; CI 95%= 1.22-2.07; p= 0.001) with heterogeneity of I2=96%, p< 0.001. Conclusion: Stress and anxiety increased the behavior of alcoholic beverage consumption in early adults.. Keywords: stress, anxiety, alcohol consumption. Correspondence: Windya Kartika Paramita. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: windyakartikap@gmail.com. Mobile: +6282227841414.